Venous blood lactate increase after vertical jumping in volleyball athletes - Chamari, K.; Ahmaidi, S.; Blum, J. Y.; Hue, O.; Temfemo, A.; Hertogh, C.; Mercier, B.; Prefaut, C.; Mercier, J. (European Journal of Applied Physiology, 2001)
The aim of this study was to test the hypothesis that venous blood lactate concentrations ([La-]) would vary from the beginning of brief exercise. Maximal vertical jumping was used as a model of brief intense exercise. Eleven healthy male volleyball players, aged [mean (SE)] 18.5 (0.7) years, performed three exercise tests with different protocols, each separated by quiet seated recovery periods of 45 min. After the first test, consisting of a single maximal jump [lasting 0.6 s for the pushing phase, and in which the subjects jumped 64 (2.2) cm], forearm venous [La-] increased significantly with respect to rest at 1 min (t1), 3 min (t3), and 5 min (t5) of recovery. The second test, comprising six maximal jumps, each separated by 20-s recovery periods, resulted in an unchanged [La-] with respect to the baseline value. After the third test [i.e., six consecutive maximal jumps that lasted a total of 7.36 (0.33) s], [La-] increased significantly at t3 and t5 with respect to the pre-test value (F=10.3, P<0.001). We conclude that a significant venous [La-] increase occurs after vertical jumping. This result may be explained by the activation of lactic anaerobic metabolism at the very onset of exercise, which participates in energy production and/or in the resynthesis of the phosphocreatine that was used during such brief exercise.